2015
DOI: 10.4103/2008-7802.151822
|View full text |Cite
|
Sign up to set email alerts
|

Current status of the clinical epidemiology of myocardial infarction in men and women: A national cross-sectional study in Iran

Abstract: Background:Cardiovascular disease is the main reason for mortality in men and women. Clinical epidemiology of myocardial infarction (MI) in men and women has not been yet studied in Iran, one of the largest Middle East countries in South-Western Asia. This study was conducted to determine the clinical epidemiology of MI in men and women in Iran.Methods:This hospital-based, cross-sectional study used the data of 20,750 MI patients in Iran in 2012 (the codes I22, I21, I24, and I25.2). Univariate comparisons used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 21 publications
(24 reference statements)
0
14
0
Order By: Relevance
“…Myocardial infarction (MI) has the highest contribution among cardiovascular diseases in Iran. [ 5 6 ] In 2012, only 4% of 45–64 years old population and 1% of 15–44 years old population were free of cardiovascular diseases risk factors in both men and women in Iran. [ 7 ] Individual risk factors of MI and the associated mortality have been examined in different countries, including Iran.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Myocardial infarction (MI) has the highest contribution among cardiovascular diseases in Iran. [ 5 6 ] In 2012, only 4% of 45–64 years old population and 1% of 15–44 years old population were free of cardiovascular diseases risk factors in both men and women in Iran. [ 7 ] Individual risk factors of MI and the associated mortality have been examined in different countries, including Iran.…”
Section: Introductionmentioning
confidence: 99%
“…[ 8 9 ] The association of seasons, income, socioeconomic status, individual and clinical risk factors, and geographic and environmental factors with mortality due to MI has been already investigated. [ 6 10 11 12 13 ] Mechanisms of geographic and environmental factors could explain the association between cardiovascular diseases and temperature. [ 10 ] Activation of the sympathetic nervous system and secretion of catecholamine are increased in response to cold temperature, which could result in an increase in blood pressure through increased heart rate and peripheral vascular resistance.…”
Section: Introductionmentioning
confidence: 99%
“…[14] In Iran, MI patients with stroke history appear to control and mitigate the risk factors themselves. [1824] Our study is the first report in Iran and indicated that the pattern of determinants of hospital MI mortality with and without a stroke is various. Therefore, adopting an appropriate strategy for the treatment and prevention of death in the two groups of the patients requires close attention to the characteristics of each group of the patients.…”
Section: Discussionmentioning
confidence: 82%
“…[161718] According to projections, stroke continues to be the second leading cause of mortality worldwide till 2030. [19] Urbanism, increased life expectancy, reduction in childbirth, aging and elderly population, epidemiological changes, socioeconomic status, geographical conditions, and lifestyles such as poor diet, stress, and low mobility are the main causes of the burden of noncommunicable diseases, particularly stroke.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 4 ] The relationship between the air pollution, temperature, relative humidity, precipitation, altitude, and mortality due to the diseases such as respiratory and cardiovascular have been identified and reported in industrialized countries. [ 5 6 7 8 9 10 11 ]…”
Section: Introductionmentioning
confidence: 99%